Transfer of different exogenous fatty acids into milk and muscle in dairy cows (2011)
ABSTRACT: This study investigated the effect of three different dietary fatty acids (FA) supplements on milk and muscle total fatty acid composition of German Holstein cows (first lactation, 92 days in milk, n=18). Ten weeks feeding of saturated, n-3 and n-6 enriched fat (3.1% of DM) affected the milk fat yield, fatty acid composition of milk and muscle. Exogenous n-3 fatty acid supply (2.7 % linseed oil+ 0.4 % DHA algae of DM) caused significantly higher concentration of n-3 PUFA in milk and intramuscular fat. Exogenous n-6 FA supplies (2.7 % sunflower oil of DM) and 0.4 % DHA algae increased linoleic acid only in muscle. Feeding plant oil/algae to dairy cows decreased significantly the content of saturated FA in milk. Contrary to this there was a tendency for a higher deposition of SFA in muscle fat.